The social cost of automobility, cycling and walking in the European Union. - Gössling, Stefan; Choi, Andy; Dekker, Kaely; Metzler, Daniel (Elsevier, 2019)
Cost-benefit-analyses (CBA) are widely used to assess transport projects. Comparing various CBA frameworks, this paper concludes that the range of parameters considered in EU transport CBA is limited. A comprehensive list of criteria is presented, and unit costs identified. These are used to calculate the external and private cost of automobility, cycling and walking in the European Union. Results suggest that each kilometer driven by car incurs an external cost of €0.11, while cycling and walking represent benefits of €0.18 and €0.37 per kilometer. Extrapolated to the total number of passenger kilometers driven, cycled or walked in the European Union, the cost of automobility is about €500 billion per year. Due to positive health effects, cycling is an external benefit worth €24 billion per year and walking €66 billion per year. CBA frameworks in the EU should be widened to better include the full range of externalities, and, where feasible, be used comparatively to better understand the consequences of different transport investment decisions.
Keywords: Verkehrskosten; Autoverkehr; Fahrradverkehr; Fußgängerverkehr; Kosten-Nutzen-Analyse; Soziale Kosten; Externe Kosten